2009
DOI: 10.5688/aj7306108
|View full text |Cite
|
Sign up to set email alerts
|

Continuing Education Course to Attain Collaborative Comprehensive Medication Review Competencies

Abstract: Objective. To implement a long-term continuing education course for pharmacy practitioners to acquire competency in and accreditation for conducting collaborative comprehensive medication reviews (CMRs). Design. A 1½-year curriculum for practicing pharmacists that combined distance learning (using e-learning tools) and face-to-face learning was created. The training consisted of 5 modules: (1) Multidisciplinary Collaboration; (2) Clinical Pharmacy and Pharmacotherapy; (3) Rational Pharmacotherapy; (4) CMR Tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…In addition, over 90% of participants reported that the workshop changed their knowledge and attitudes about female sexual health; one of the primary goals of the workshop was to increase healthcare professionals' intent to ask their patients about sexual health by changing their knowledge of and attitudes about the topic. Consistent with prior research findings in the general area of CE (Houge 1988;Leikola et al 2009;Miller and Byers 2009), participants at the current workshop report planning to use information, techniques and resources provided during the workshop in their clinical practice.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, over 90% of participants reported that the workshop changed their knowledge and attitudes about female sexual health; one of the primary goals of the workshop was to increase healthcare professionals' intent to ask their patients about sexual health by changing their knowledge of and attitudes about the topic. Consistent with prior research findings in the general area of CE (Houge 1988;Leikola et al 2009;Miller and Byers 2009), participants at the current workshop report planning to use information, techniques and resources provided during the workshop in their clinical practice.…”
Section: Discussionsupporting
confidence: 53%
“…Medication reviews require clinical competence that community pharmacists do not routinely have in Finland without additional training. 28,29 This reflects to preceptors' skills to introduce students to use databases containing more clinically oriented pharmacotherapeutic and medical information. 19 If pharmacy preceptors do not have the skills necessary to utilize these resources, it would be difficult for them to teach students.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in the field of pharmacy and pharmacology, several publications on the use of e-learning for postgraduates at universities [14][15][16] as well as at other educational institutions [17,18] have demonstrated that e-learning may gain increased importance in this sector in the future. The results of this investigation show that students are aware that e-learning offers potential for life-long learning and that they are willing to use e-learning after graduation for further professional development.…”
Section: Resultsmentioning
confidence: 99%